Advancing the future of physical activity guidelines in Canada: an independent expert panel interpretation of the evidence - Blair Steven N; Reeder Bruce; Riddoch Chris J; Kesäniemi Antero; Sørensen Thorkild IA (BMC, 2010)
Abstract The Canadian Society for Exercise Physiology, in partnership with the Public Health Agency of Canada, has initiated a review of their physical activity guidelines to promote healthy active living for Canadian children, youth, adults and older adults; previous guidelines were released in 2002, 2002, 1998 and 1999 respectively. Several background papers from this project were published recently and provide foundation evidence upon which to base new guidelines. Furthermore, comprehensive systematic reviews were completed to ensure a rigorous evaluation of evidence informing the revision of physical activity guidelines for asymptomatic populations. The overall guideline development process is being guided and assessed by the AGREE II instrument. A meeting of experts was convened to present the evidence complied to inform the guideline revisions. An independent expert panel was assembled to review the background materials and systematic reviews; listen to the presentations and discussions at the expert meeting; ask for clarification; and produce the present paper representing their interpretation of the evidence including grading of the evidence and their identification of needs for future research. The paper includes also their recommendations for evidence-informed physical activity guidelines.